1977
DOI: 10.1177/25.5.864237
|View full text |Cite
|
Sign up to set email alerts
|

Ultracytochemical demonstration of monoamine oxidase activity in nervous and non-nervous tissue of the rat.

Abstract: A method is described for the ultrastructural localization of the enzyme monoamine oxidase based on the formation of an osmiophilic formazan from the tetrazolium salt (2-(2'-benzothiazolyl)-5-styrl-3-(4'-phthalhydrazidyl) tetrazolium chloride) (BSPT) and using tryptamine as substrate. It was tested in rat heart, liver, adrenal cortex and medulla, kidney, pineal gland, cerebral cortex and cerebellar cortex and was found to provide good ultrastructural preservation, high contrast of the specific, enzyme-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…When examined under transmission electron microscopy, MAOB was localized to the mitochondrial outer membrane of hepatocytes.These results are in general agreement with those of Shannon et al (1974) and Muller and Lage (1977). By…”
supporting
confidence: 91%
See 2 more Smart Citations
“…When examined under transmission electron microscopy, MAOB was localized to the mitochondrial outer membrane of hepatocytes.These results are in general agreement with those of Shannon et al (1974) and Muller and Lage (1977). By…”
supporting
confidence: 91%
“…For the first time, using a double-labeling immunofluorescence histochemical method for laser microscopy, we reported that in rat liver, no MAOB immunoreactivity was found in endothelial cells, hepatic stellate cells, or in Kupffer's cells. Though there were reports that MAOB is localized on capillary endothelial cells of rat tongue (Xu et al, 2002), hepatic stellate cells of rat liver (Muller and Lage., 1977), and Kupffer's cells of human peripheral blood (Seiler et al, 1995). In fact, at electron microscopic level, we also found no MAOB was expressed in endothelial cells, hepatic stellate cells, or in Kupffer's cells (data not show).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were two kinds of mitochondria in pancreatic islet B cells: one contained MAOB on their outer membranes, but a substantial proportion of them lacked this enzyme. This finding may be attributable to one or more of the following factors (Shannon et al 1974;Muller and Lage 1977): (a) different physiologic regions or states of the outer membranes, in which case the observed activity represents the true distribution of active MAOB; (b) uneven fixation that destroys some active enzyme sites; or (c) artificial, which was made by cutting. Further research is needed to understand the exact reasons for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral organs, MAOB activity has been shown to be far more abundant in the outer membrane fraction of rat liver mitochondria than in the inner membrane fraction [28]. Using an enzyme histochemical method employing a substrate common to both MAOA and MAOB, subcellular localization of MAO activity has been examined in the heart, liver, adrenal cortex and medulla, and kidney of rats [9,24]. However, to our knowledge, no previous study has examined, by immunohistochemistry, the individual subcellular localization of MAOA or MAOB enzyme in peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%